2005
DOI: 10.1111/j.1529-8817.2005.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of FRAXA Intermediate Allele Phenotype in A Longitudinal Sample

Abstract: SummaryThe FRAXA trinucleotide repeat at Xq27.3 gives rise to fragile X syndrome when fully expanded, and both premature ovarian failure (POF) and fragile X tremor and ataxia syndrome (FXTAS) when in the premutation range. Reports of phenotypic effects extending into the intermediate repeat range are inconsistent but some studies suggest that these smaller expansions predispose to special educational needs (SEN). This study utilises the Avon Longitudinal Study of Parents and Children (ALSPAC) cohort to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…A population screening of 1013 boys with learning disabilities and their mothers (n = 760) showed a significant excess of gray zone alleles (41–60 CGG) in the affected boys 7. However, a follow‐up study in boys with special education needs (n = 5084) did not confirm this result 9. Primary ovarian insufficiency has been shown to be increased in women with 41–58 CGG repeats 6, 10.…”
Section: Discussionmentioning
confidence: 99%
“…A population screening of 1013 boys with learning disabilities and their mothers (n = 760) showed a significant excess of gray zone alleles (41–60 CGG) in the affected boys 7. However, a follow‐up study in boys with special education needs (n = 5084) did not confirm this result 9. Primary ovarian insufficiency has been shown to be increased in women with 41–58 CGG repeats 6, 10.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38] Nevertheless, a definitive association between the presence of IAs and clinical manifestations remains unclear. [39][40][41] The clinical phenotypes associated with premutation alleles and severity of neurological problems associated with the FMR1 premutation allele. Finally, the progression of FXTAS has been shown to be more rapid in patients that have been exposed to environmental toxins such as chronic use of addictive substances (opiates, alcohol, and cocaine) or chemotherapy.…”
Section: Clinical Involvement In Fmr1 Premutation Carriersmentioning
confidence: 99%
“…Hessl et al (2005) reported elevated levels of mRNA in individuals with premutations who had psychiatric symptoms; and MRI changes were found to correlate with anxiety in women with FMR1 premutations, even in those without a clinical diagnosis of FXTAS (Adams et al, 2010 (Loesch et al, 2009b), primary ovarian insufficiency (Bodega et al, 2006), and autism and cognitive disabilities (Aziz et al, 2003;Loesch et al, 2009a). However, these findings have not consistently been supported by other studies (Ennis et al 2006;Bennett et al, 2010) and can be difficult to interpret due to inconsistencies in the way researchers have defined the intermediate range. Additional research is needed to clarify the clinical relevance of intermediate alleles.…”
Section: Other Premutation-associated Issuesmentioning
confidence: 97%